'Management multiple myeloma during pregnancy: a case report and review'. Issue 2 (10th December 2014) - Cabañas‐Perianes, Valentin; Macizo, Maribel; Salido, Eduardo; Blanquer, Miguel; Araico, Fernando; Melero‐Amor, Antonia; Garcia‐Candel, Faustino; Muñoz‐Garcia, Maria Isabel; Martinez‐Villanueva, Miriam; Muñoz‐Esparza, Carmen; Guzmán‐Aroca, Florentina; Pérez‐López, Raúl; et al.
Abstract: Multiple myeloma (MM) is a hematologic neoplasm characterized by plasma tumor cell proliferation in the bone marrow. It's a rare malignancy before a 40‐year‐old and it is extremely uncommon during pregnancy. We report the case of a 37‐year‐old woman with a newly diagnosed IgG λ MM (Durie–Salmon stage IIIA, International Staging System II and good prognosis cytogenetic) at the 27th week of her pregnancy. Our management during pregnancy, the delivery, and initiation of anti‐myeloma treatment with bortezomib, lenalidomide, and dexamethasone are published. There are a few reviews reporting the most common features and management of MM during pregnancy. We perform a comprehensive review of all 32 cases reported between 1965 and 2014 in which a MM was diagnosed during pregnancy including score, cytogenetic results, labor characteristics, and response to therapy. About 53% of pregnant women did not start treatment before partum. Cesarean section was the most common form of delivery (82%). About 88% of newborns were healthy, although most of them were premature (73%). Management of a MM diagnosed during pregnancy should be based on the presence of myeloma‐related organ damage to secure survival of the mother without fetal adverse effects related to treatment. Serial fetal ultrasound may be helpful in order to avoid complications. The cesarean section may be preferred depending on maternal and fetus prognosis. Whole‐body diffusion‐weighted imaging minimal response could be an appropriate technique to discard plasmacytomas during pregnancy in critical situations such as the appearance of symptoms of spinal cord compression. Therapeutic choices should be agreed with the pregnant after a thorough discussion of the prognostic factors of the disease and the potential risk for the fetus and the patient. While awaiting partum, dexamethasone is a non‐toxic treatment. Triple therapy including a proteasome inhibitor should be started quickly after delivery. Copyright © 2014 John Wiley & Sons, Ltd.